Marital biography and health in old age: insights from European Survey Data - Schütz, Johanna (2019)
Abstract: The research project is motivated by the well-known health and longevity advantage of married persons over the unmarried. In times of population ageing and changing marital behaviour, an investigation of the marriage-health nexus by applying a life course perspective is relevant. Instead of merely considering current marital status, the study compares marital biographies and the association with health in old age. Using the Survey of Health, Ageing and Retirement in Europe (SHARE), I investigate cross-country differences of marital and partnership biographies of a sample of more than 22,000 Europeans above age 50, from 14 European countries. I discuss national differences and similarities of the following components of the marital life course: current marital status, number of marriages, sequencing and timing of marital transitions, duration of marital status, number, type and timing of non-marital partnerships. In a second step, I analyse the association of the marital life course with health status in later life, using objective indicators of physical and cognitive health (grip strength, expiratory air flow, memory, verbal fluency). I address possible selection effects by adjusting for health and cognitive status during childhood. Results obtained by cross-sectional regressions show that married Europeans have better physical and cognitive health outcomes, compared to the never married and the separated. Widowed Europeans are disadvantaged in terms of cognitive health, but not physical health. With respect to marital biography, marriage before age 20 and remarriage are related to health deficits in old age, whereas length of a marriage shows no effect. Also multiple marital losses seem to affect physical health negatively. A longer period of widowhood is related to a decrease in cognitive health – regardless of current marital status. The latter finding is also supported by longitudinal fixed-effects regressions that draw on over 55,000 observations from 17 European countries and Israel.
Keywords: Hochschulschrift